International economics : theory & policy. - Krugman, Paul R.; Obstfeld, Maurice; Melitz, Marc J. (Pearson, 2023)
A balanced approach to theory and policy applications, this book provides engaging, balanced coverage of the key concepts and practical applications of the two main topic areas of the discipline. For both international trade and international finance, an intuitive introduction to theory is followed by detailed coverage of policy applications. With this new tenth edition, the author team of Nobel Prize-winning economist Paul Krugman, renowned researcher Maurice Obstfeld, and Marc Melitz of Harvard University continues to set the standard for international economics courses.